A Study on the Present Status and Issues of Organic Paddy Rice Expansion in Northeast Semi-arid Region of China: The Case Study of T Farm, Baicheng City, Jilin Province - Ma, Jian; Abdullah, Alias; Kobayashi, Hajime (WILAYAH: The International Journal of East Asian Studies, 2013)
The abstract is not available. To access, please order the printed version or browse the electronic version of this article.